An Analysis on Thematic Progression Patterns of Boris Johnson’s Speech - Putu Nur Ayomi; Larasati, Kadek Dwi; I Gusti Ayu Vina Widiadnya Putri (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
The study mainly focuses with the Theme Rheme and Thematic Progression Pattern observed in Boris Johnson's address as Prime Minister of the United Kingdom. The study's goal is to examine the sort of Theme Rheme and Thematic Progression Patterns discovered in the speech text. To examine the data, the study employed a qualitative method with a descriptive design. The data is derived from Prime Minister Boris Johnson's speech text. The data was evaluated using Halliday's (1994,2004) theory to analyze the Theme and Rheme and Paltridge's (2006) theory to analyze the Thematic Progression Pattern. According to the study, Circumstantial Adjunct as Topical Theme is the most dominant in the Thematic Progression Patterns, it is found that Reiterated/Constant Theme Pattern is the most dominant in the Thematic Progression Pattern.